A Turning Trash into Treasure: How Composting and Eco-enzymes Can Revolutionize Waste Management and Add Value: ECO-ENZYMES AND ADD VALUE - Vincentia Irene Meitiniarti; Liska Simamora; Damara Dinda Nirmalasari Zebua (Cita konsultindo, 2024)
Managing organic waste through composting and eco-enzyme production offers environmental and economic advantages. Composting reduces methane emissions, enhances soil quality, and boosts agricultural yields, while eco-enzymes provide a novel waste management solution. This study compares the added value of food and garden waste in eco-enzyme and compost production, emphasizing their potential for sustainable resource utilization and economic gain. The research involves waste collection, production, quality analysis, and added value assessment. Compost and eco-enzymes are made from various waste compositions, with quality analysis covering nutrient content and enzyme activity. Economic analysis highlights the viability of composting and eco-enzyme production. Despite challenges such as low material content and unexpected water increase with EM4, both methods show promise. Composting yields IDR2,142.86 with a 65% added value ratio, while eco-enzymes earn IDR69,964 with a 94% ratio, offering benefits like room freshening and higher profits.